Social Justice and Diversity in Zambia: The Role of Civic Education and Teachers - Chivunda, Kaumba; Kabombwe, Yvonne; Mwanza, Christine; Mupeta, Sydney (Asian Journal of Education and Social Studies, 2023)
This article explores the role civic education plays in social justice and diversity in Zambia from the civic education teacher’s perspective as well as establish the extent to which teacher’s themselves are actively engaged in social justice and diversity. Predicated on the fundamental role civic education plays in teaching and promoting diversity and social justice, it is highly expected that civic education teachers should be the lodestars in undertaking this activity. It is noted that teachers of civic education can bring about social justice in society; this can be achieved through active participation in local communities and consolidating the teaching of democracy, human rights and promotion of participation within people’s local communities and global level for social justice. Therefore, the teaching for diversification is of great significance in the delivery of Civic Education in Zambia both at teacher training and secondary school level. Anchored on the explanatory design as a methodological bedrock, this study found that teachers where not actively engaged with issues of diversity. The study concludes that there is little to no engagement among teachers in diversity and in bringing about social change especially on matters that affect the wider community. This is partly attributed to the impractical nature in which Civic Education is delivered at secondary school or tertiary level. The study recommends that different approaches to the teaching of civic education must be introduced in the civic education curriculum.